2015
DOI: 10.1007/s00586-015-4274-6
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar spinal degenerative “microinstability”: hype or hope? Proposal of a new classification to detect it and to assess surgical treatment

Abstract: In patients with low back pain and negative dynamic X-Rays, an accurate analysis of the radiological exams (CT, MRI, X-Rays) allows to formulate a diagnosis of suspect MI with a good predictive value. This situation opens many clinical and medicolegal scenarios. The preliminary results seem to validate the test with a good predictive value, especially towards ASD, but they need further studies. On the basis of the results obtained, the test seems to allow a good classification of the dysfunctional phase of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 23 publications
0
21
0
1
Order By: Relevance
“…In the final cohort were included only patients with a physiological lordotic lumbar curve.All the patients included in the final cohort suffered from a purely lumbar spinal stenosis L1–L5.In order to minimize the influence of the individual differences in the lumbar FSU degeneration, according to a previously published score [14] we included only patients with intervertebral disc that scored at least 3 or 4 according to Pfirrmann scale.Patients with a history of previous lumbar, thoracic or cervical spine surgery, as well as patients with history of spine fractures, dislocations or spine inflammatory diseases were excluded because of the possibility that a previous spine surgery or condition could jeopardize the entire spine biomechanics and thus confound results.Unavailable or incomplete surgical or clinical records,Patients operated on (in surgical subgroup) presenting surgical complication such as epidural hematoma, surgical infections and incidental durotomy.Patients who did not accept re-evaluation, dead, too sick or not attending the follow-up. When writing the present paper, we noticed that the exclusion of patients who did not accept revaluation could include patients who had an extremely good outcome with conservative management and did not feel a re-evaluation would be necessary and patients who experienced an extremely unsatisfying outcome or an unsatisfying medical relationship with the senior author (R.C.)…”
Section: Methodsmentioning
confidence: 99%
“…In the final cohort were included only patients with a physiological lordotic lumbar curve.All the patients included in the final cohort suffered from a purely lumbar spinal stenosis L1–L5.In order to minimize the influence of the individual differences in the lumbar FSU degeneration, according to a previously published score [14] we included only patients with intervertebral disc that scored at least 3 or 4 according to Pfirrmann scale.Patients with a history of previous lumbar, thoracic or cervical spine surgery, as well as patients with history of spine fractures, dislocations or spine inflammatory diseases were excluded because of the possibility that a previous spine surgery or condition could jeopardize the entire spine biomechanics and thus confound results.Unavailable or incomplete surgical or clinical records,Patients operated on (in surgical subgroup) presenting surgical complication such as epidural hematoma, surgical infections and incidental durotomy.Patients who did not accept re-evaluation, dead, too sick or not attending the follow-up. When writing the present paper, we noticed that the exclusion of patients who did not accept revaluation could include patients who had an extremely good outcome with conservative management and did not feel a re-evaluation would be necessary and patients who experienced an extremely unsatisfying outcome or an unsatisfying medical relationship with the senior author (R.C.)…”
Section: Methodsmentioning
confidence: 99%
“…Spinal pain is one of the most common medical conditions of the 21 st century [1][2][3][4][5][6][7]. Recent studies have shown that sacral pain occurs in as many as 80% of adults and 39.5% of adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…We consider the flexion/extension radiograph a useful examination in the assessment of lumbar instability, and we recently reported that instability is sometimes not evident at static examinations and the dynamic examination can reveal it. In these cases it is called microinstability [3]. Microinstability has clinical relevance and may be helpful to distinguish patients who require decompression alone from those who require decompression plus fixation [1].…”
mentioning
confidence: 99%